Meningkatkan Hasil Belajar Pendidikan Agama Katolik Melalui Metode Problem Based Learning Kelas VIII SMP Negeri 3 Tapian Nauli - Kristina Fandinata Silaban (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Humans who are living creatures with reason have the potential to continue to develop. One of the human developments is Catholic religious education in schools. Learning Catholic Religious Education encourages students to become faithful individuals who are able to live and realize their faith in everyday life. The independent curriculum emphasizes the profile of Pancasila students. In this classroom action research, the researcher emphasizes the dimensions of faith in God Almighty and noble character and the dimension of critical reasoning. This study describes the process of implementing the problem-based learning (PBL) model in Catholic Religious Education learning for class VIII and analyzes its impact on student motivation and learning activities. Through observation, interviews, and document analysis, it was found that PBL succeeded in creating an active and student-centered learning environment. Students were more involved in the learning process, showed increased learning motivation, and developed collaboration skills. The evaluation results showed a significant increase in student learning outcomes after the implementation of PBL. The objectives of this study were (1) To determine the improvement in student learning outcomes through Problem Based Learning for Class VIII of SMP Negeri 3 Tapian Nauli. (2) Knowing the increase in target achievement through the Problem Based Learning model in Class VIII of SMP Negeri 3 Tapian Nauli. The interaction and communication between teachers and students and communication between students greatly supports learning activities.